Educação, desenvolvimento e migração em cidades médias de Minas Gerais equipadas com Instituto Federal de Educação, Ciência e Tecnologia - Adriana Mota Barbosa (2013)
The interfaces between Education and the development and migration in medium-size cities equipped with Federal Institutes of Education, Science and Technology are the central theme of this study.The reflection and the research investigate how the State has been acting in the territory as a developer of training policies, qualifying the workforce; they discuss the relations established between economic and demographic development. Minas Gerais is chosen as the analytical space for the understanding of multiple relations regarding the peculiar profile of its Rede Federal de Educação Profissional, Científica e Tecnológica. To maintain analytical rigour in the purposes of this thesis, it examines, considering the so called globalization, which are the connections between the Knowledge Society, the capitalist State and the production oftechnology and its repercussions in Brazil. The study rescues the metamorphosis of the concept of average city and the role of migration on the economic and demographic dynamism of those places, and scans the trajectory of Brazilian technical education, from its genesis to the present day. Backed by the research literature and in line with the methodology adopted, the mediumsize cities of Minas Gerais that have a Federal Institute and demographic and income growth in the period of 2000 to 2010 were selected. Comparisons were made with municipalities of the same size that do not have the institution. Specifically, this study investigates the presence of educational institutions and the relation with the population likely to occupy the vacancies offered, and also the characteristics of the places that hold these institutions and attract migrant population.Thus, migration, migration balance, the median income of the urban employed population, educational profile and occupation of migrants and nonmigrants are some of the variables that are part of the research. It refers to data provided by the Instituto Brasileiro de Geografia e Estatística and Fundação João Pinheiro such as population censuses, the Pesquisa Nacional de Amostra Domiciliar and Índice Mineiro de Responsabilidade Social. The empirical research is confronted with the theoretical framework constructed to infer the validity of the hypothesis and the general findings prove it.